Improvements in Physical and Mechanical Properties of Asphalt by Addition of Low-cost Few-layers Graphene (FLG) - Amun Amri; M. Sugandi; Syelvia Putri Utami; Muhammad Shalahuddin; Sulistyo Saputro (AMTS and Faculty of Engineering - Universitas Riau, 2022)
Physical and mechanical properties of asphalt have been improved by adding of few-layers graphene (FLG). FLG was obtained from a simple, low-cost and environmentally friendly liquid shear exfoliation method using a kitchen blender. The melted asphalt at temperature of 150oC was mixed with FLG at various concentrations (10 mg/ml, 20 mg/ml and 30 mg/ml) and contents (0 wt%, 3 wt%, 6 wt%, and 9 wt%) by weight of asphalt. The homogenized mixture was taken for penetration and softening point tests, while the mixing with aggregates was carried out for Marshall stability and asphalt concrete flow tests. The characteristics of void in mixture (VIM), void filled with asphalt (VFA), and void in mineral aggregate (VMA) were also investigated. The penetration values decreased (or the asphalt hardness increased) linearly with increasing of FLG concentration and FLG content. The softening point of asphalt increased as the increasing of FLG concentration and FLG content in asphalt with the average softening point increase of about 5%. The Marshall stability and asphalt concrete flow increased with increasing of FLG concentrations and FLG content. However, the addition of FLG did not affect the VIM, VFA or VMA values. Overall, the addition of FLG improves the physical and mechanical properties of asphalt and has promising prospects due to low-cost and eco-friendly nature of FLG.